Inner Security in Media from the perspective of social science and media studies (Sociología y Tecnociencia, 2012)
Security and entertainment are moving closer together. The term Securitainment expresses in this context, the mediation of security through entertainment formats. This will open a new space for Internal Security, which includes its own actors and patterns of interpretation. This space is portrayed in the media and follows the logic of media for attention but is also part of the process of social control. The mass media are therefore an instance of the design of internal security, social control and an interpretation producer. Mass media become actors of the internal security. They provide a symbolic representation of security.